Perkembangan Masa Bayi - Oti Aprillia; Nadia Gufran; Linda Yarni (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to explain the development of infancy in the form of characteristics, developmental tasks, physical development and psychological functions. This research uses a qualitative approach with a literature study, namely a method of collecting theories from books and journal articles. The results of this study conclude that the characteristics of infancy are that infancy is a real period, a period where growth and change are rapid, a period of reduced dependence, a period of increased individuality, the beginning of socialization, the beginning of the development of sex role classification, an interesting period, the beginning of creativity, and a dangerous period. The developmental tasks of infancy are learning to walk, eating solid food controlling the elimination of body waste, achieving good physiological stability, learning the basics of speech, learning to relate emotionally to others and forming simple concepts about social and natural reality. The physical development of infancy includes weight, height, physical proportions, bones, muscles and fat, body build, teeth, nervous system, and the development of sense organs. Infancy is also a time of establishing fundamental growth patterns for sleeping, eating and toileting.